2017
DOI: 10.1097/gox.0000000000001398
|View full text |Cite
|
Sign up to set email alerts
|

Goldilocks Mastectomy: A Safe Bridge to Implant-Based Breast Reconstruction in the Morbidly Obese

Abstract: Background:Reconstructive surgeons are encountering an increasing number of obese women requiring postmastectomy reconstruction. These patients are poor candidates for autologous and prosthetic-based reconstructions as they have a high rate of reconstructive failure, surgical complications, and poor aesthetic outcomes. We demonstrate here the utility of the previously described Goldilocks mastectomy with free nipple grafts as a safe bridge to second stage implant-based breast reconstruction.Methods:Ten consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 9 publications
(11 reference statements)
0
19
0
Order By: Relevance
“… 8 In this, skin sparing mastectomy done through wise incisions utilizes the residual cutaneous flaps to auto-augment the breast mound. 9 Despite minor discrepancies in NAC levels in both cases, long-term symmetry and patient satisfaction were excellent…”
Section: Discussionmentioning
confidence: 83%
“… 8 In this, skin sparing mastectomy done through wise incisions utilizes the residual cutaneous flaps to auto-augment the breast mound. 9 Despite minor discrepancies in NAC levels in both cases, long-term symmetry and patient satisfaction were excellent…”
Section: Discussionmentioning
confidence: 83%
“…Postmastectomy reconstruction is typically performed using implant-based techniques [1,5,10,11]. Although the majority of patients have a completely uneventful postoperative course, unfortunately, some patients experience complications [12], one of the most common of which is seroma development [12].…”
Section: Discussionmentioning
confidence: 99%
“…In only a small percentage of women who are large breasted, with ptosis and elevated BMI, can a reconstructed breast of appropriate volume and proportion be constructed in a single stage. 8 We have previously shown that second-stage implant placement 9 or lipotransfer 10 can enhance the final result but carry with them the risks of a prosthetic and the more than likely need for additional fat-grafting surgeries, respectively. These approaches, at a minimum, require 2 surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The donor site morbidity associated with the LICAP flap is minimal and does not have the same wound breakdown rate as a latissimus flap where the skin is often undermined, and the muscle mobilized. 9…”
Section: Discussionmentioning
confidence: 99%